Syed Abu Tahir A/L Mohamed Esmail V. P.P: Some Reflections - George, Mary (Journal of Malaysian and Comparative Law, 2019)
The case of Syed Abu Tahir A/L Mohamed Esmail V. P.P a criminal appeal case involving kidnapping, rape and sentencing. This casenote only addresses the issue of kidnapping - kidnapping from lawful guardianship. The impugned section is section 361 of the Penal Code.